The Introduction to Special Issue on Student Entrepreneurship - Parente, Roberto; Feola, Rosangela (Piccola Impresa / Small Business, 2021)
This Special Issue would represent a forum for scholar inthe field to further accrue knowledge on student entrepreneurshipand the five papers included in the issue areauthored by scholars from around the globe on a differentarray of student’s entrepreneurship timely topics.